2005
DOI: 10.1002/chem.200401065
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Seven‐Membered Rings: Ruthenium‐Catalyzed Intramolecular [5+2] Cycloadditions

Abstract: The Ru-catalyzed intramolecular [5+2] cycloaddition of cyclopropylenynes is investigated with respect to the regio- and diastereoselectivity as well as the functional group compatibility of the reaction. Evidence for the mechanism as occurring through a ruthenacyclopentene intermediate is elucidated from 1) the study of the diastereoselectivity of the cycloaddition; 2) the effect of variation of substituents on the regioselectivity of cyclopropyl bond cleavage in 1,2-trans- and 1,2-cis-disubstituted cyclopropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 52 publications
0
62
0
1
Order By: Relevance
“…Seven-membered rings were prepared by ruthenium-catalyzed [5 + 2]cycloisomerization of 1-cyclopropyl-6-yne-1-enes (Eq. (285)) [1368]. In contrast nickel catalyzed the formation of five-membered rings from 1-cyclopropyl-6-yne-1-enes (Eq.…”
Section: Cycloisomerizationsmentioning
confidence: 96%
“…Seven-membered rings were prepared by ruthenium-catalyzed [5 + 2]cycloisomerization of 1-cyclopropyl-6-yne-1-enes (Eq. (285)) [1368]. In contrast nickel catalyzed the formation of five-membered rings from 1-cyclopropyl-6-yne-1-enes (Eq.…”
Section: Cycloisomerizationsmentioning
confidence: 96%
“…The comparison with the noncatalyzed cycloaddition allowed one to see how the rhodium catalyst transformed a two-step process with high barriers into a multi-step process with lower activation energies. [ 35] This methodology was more recently applied by these authors to the [5 + 2] cycloaddition of cyclopropylenynes such as 45a-l. [36] This study reported the scope of these reactions regarding the functional group tolerance of the reaction, and the length and nature of the tether between alkyne and VCP. A broad range of vinylcyclopropyl-alkyne substrates 45a-l reacted under ambient conditions (room temperature in acetone, DMF or DCE), providing, in the presence of 5-10 mol% of the Ru catalyst, the corresponding cycloadducts 46a-l in high yields.…”
Section: Intermolecular Rhodium-catalyzed [5 + 2] Cycloadditionsmentioning
confidence: 99%
“…[36] As shown in Scheme 25, a series of variously functionalized tricyclic products 54a-i could be synthesized with up to 90% de. These authors have reported another extension of this methodology applied to the development of the first total synthesis of the natural biologically active product, (+)-frondosin A.…”
Section: Intermolecular Rhodium-catalyzed [5 + 2] Cycloadditionsmentioning
confidence: 99%
See 2 more Smart Citations